1997
DOI: 10.1007/s11357-997-0015-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the antioxidant turmeric on lipoprotein peroxides: Implications for the prevention of atherosclerosis

Abstract: Extracts from the rhyzome of Curcuma Ionga are widely used as food additives in India and other Asiatic and Central American countries. It has been shown that these extracts ("turmeric"), as well as "curcumin" and related phenolic compounds isolated from Curcuma, have a powerful antioxidant action when tested in in vitro systems. Moreover, previous research from our laboratories has shown significant decreases in the levels of lipid peroxides in the blood of both mice and human subjects administered "turmeric.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Rather, PGs are released locally by a variety of cells [23, 24], including malignant cells [25], and as a response to tissue damage [26]. Under some conditions (e.g., surgery) local release can markedly increase systemic PGs levels [27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…Rather, PGs are released locally by a variety of cells [23, 24], including malignant cells [25], and as a response to tissue damage [26]. Under some conditions (e.g., surgery) local release can markedly increase systemic PGs levels [27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…The cytokines such as the tumor-necrosis factor (TNF) are produced by immune cells, and can improve the efficacy of the T cell priming and induce adaptive anti-tumor immunity (Zou, 2005). On the other hand, certain cytokines have been associated with poor patient outcomes, and reported to promote tumor growth and inhibit anti-tumor immune response (Wojtowicz-Praga, 1997; Mocellin et al, 2001; Raman et al, 2007). For example, imbalanced production of interleukin 6 (IL-6), vascular endothelial growth factor (VEGF), or macrophage colony-stimulating factor (M-CSF) inhibit adaptive anti-tumor immunity by suppressing dendritic cell maturation and activating regulatory T cells (T reg ) to aid tumor cells in evading immune-surveillance (Zou, 2005).…”
Section: Protein Secretomic Profiling As a Tool To Study The Cytokinementioning
confidence: 99%
“…42,43,46 Moreover, the treatment did not result in any significant change of the key parameters of blood coagulation. This apparent lack of toxicity was in agreement with data from the National Bureau of Standards of Hyderabad, according to which the daily adult intake of turmeric in diet (as a food additive) ranged between 0.1 and 3.8 g. In our opinion, this preliminary finding justified further work to confirm the fibrinogenlowering effects of turmeric on a larger group of subjects.…”
Section: Anticoagulant Activitymentioning
confidence: 93%
“…Previous research had already shown that this product decreased the levels of lipid peroxides and oxidized lipoproteins. 42,43 The subjects chosen were in the age group 24-75 years and were in apparent good health and held managerial, scientific, or technical jobs. After obtaining their informed consent, blood was taken from the cubital vein and fibrinogen was determined using the method of Claus.…”
Section: Anticoagulant Activitymentioning
confidence: 99%
See 1 more Smart Citation